2021
DOI: 10.1093/ejcts/ezab217
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac surgery following transcatheter aortic valve replacement

Abstract: OBJECTIVES The objective of this study was to retrospectively analyse surgical outcomes of patients undergoing secondary cardiac surgery after initial transcatheter aortic valve replacement (TAVR). METHODS Between December 2012 and February 2020, a total of 41 consecutive patients underwent cardiac surgery after a TAVR procedure at our institution. Patients who underwent emergency operations due to periprocedural complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Infective endocarditis has been reported to be the most common indication of surgery following aortic THV implantation [50]. Following THV implantation, vigilance, early diagnosis, adequate antibiotic treatment, and early surgery are essential [50,51] in cases of infective endocarditis.…”
Section: Operative Considerationsmentioning
confidence: 99%
“…Infective endocarditis has been reported to be the most common indication of surgery following aortic THV implantation [50]. Following THV implantation, vigilance, early diagnosis, adequate antibiotic treatment, and early surgery are essential [50,51] in cases of infective endocarditis.…”
Section: Operative Considerationsmentioning
confidence: 99%
“…However, previous studies have shown that TAVR prostheses can be explanted with reasonable results and no damage to adjacent structures [ 6 , 17 ]. The superior outcomes in our study may be related to the management of our patients in a high-volume heart valve center with a multidisciplinary endocarditis team approach [ 22 ].…”
Section: Commentmentioning
confidence: 99%
“…Although current guidelines consider surgery to be the best option in cases of prosthetic valve endocarditis (PVE), the current literature reports a general reluctance toward the surgical treatment of IE following transcatheter aortic valve implantation (TIE), with some patients entering palliative care upon diagnosis [ 1 , 2 , 3 , 4 , 5 ]. Infective endocarditis (IE) is the leading cause of reoperation following transcatheter aortic valve replacement [ 6 ]. Up to 90% of patients suffering from TIE undergo conservative treatment, and this has been associated with high in-hospital mortality and poor short-term survival [ 7 ].…”
Section: Introductionmentioning
confidence: 99%